Dynamic chromatin accessibility and transcriptional landscapes of porcine kidney cells during pseudorabies virus infection - Yang, Songbai; Dong, Mingyang; Shi, Haixin; Li, Xiangchen; Wang, Han; Zhou, Xiaolong; Zhao, Ayong (Frontiers in Immunology, 2026)
BackgroundPseudorabies virus (PRV) is a major swine pathogen that causes substantial economic losses. The dynamic remodeling of host cell chromatin plays a pivotal role during viral infections. However, the epigenetic mechanisms underlying PRV-host interactions remain unclear.MethodsThis study integrates ATAC-seq and RNA-seq to investigate the dynamic changes in host chromatin accessibility and gene transcription during PRV infection. The accessible chromatin regions were analyzed for enrichment in genomic features and transcription factor binding motifs. RNA-seq data were used to identify differentially expressed genes and dysregulated pathways. The two datasets were integrated to examine correlations between chromatin accessibility and gene expression.ResultsPRV infection induces a genome-wide elevation in host chromatin accessibility, which progressively intensifies throughout the course of infection. These accessible chromatin regions are predominantly enriched in promoters and binding motifs for bZIP family transcription factors, such as BATF, ATF3, and AP-1, suggesting these transcription factors may play an important role in PRV infection. RNA-seq analysis reveals that PRV infection significantly dysregulates genes involved in metabolic and immune response pathways, with extensive transcriptional suppression observed in the late stages. Integration of ATAC-seq and RNA-seq data demonstrates that chromatin accessibility is positively correlated with gene expression for the majority of differentially expressed genes. However, certain genes exhibit discordant regulation, implying the existence of more complex regulatory mechanisms.ConclusionThis study provides valuable epigenetic insights into the PRV-host interaction and establishes a theoretical framework for developing novel antiviral strategies.